Morphological, morphometric, and molecular identification of Octopus cyanea in the Waters of Kaur District, Bengkulu Province, Indonesia - AHMAD PARIANSYAH; RATIH IDA ADHARINI; DINI WAHYU KARTIKA SARI; EKO HARDIANTO (Society for Indonesian Biodiversity, 2025)
Abstract. Pariansyah A, Adharini RI, Sari DWK, Hardianto E. 2025. Morphological, morphometric, and molecular identification of Octopus cyanea in the Waters of Kaur District, Bengkulu Province, Indonesia. Biodiversitas 26: 2640-2652. Octopus is a high-value fishery resource abundant in the waters of Kaur District, Bengkulu Province. This study aimed to identify octopus species inhabiting Kaur waters through integrated morphological, morphometric, and molecular analyses. A total of 68 octopus specimens were collected (20 males and 48 females) with a sex ratio of 1:2.4. Field identification confirmed all specimens as Octopus cyanea, characterized by oval mantles, W-shaped funnels, and two rows of suckers per arm. Males possessed larger suckers and a hectocotylized third right arm. The body displayed brown and white coloration, false eye spots (ocelli), black stripes, white spots along he arms, and four small papillae. Molecular analysis using the Cytochrome c Oxidase Subunit I (COI) gene showed a 100% match with O. cyanea sequences in GenBank, confirming species identity. Morphometric analysis revealed that females had relatively larger body ratios, particularly MW/TL, ML/MW, FuL/PA, and WD/AL. Phylogenetic and genetic distance analyses demonstrated close relationship between O. cyanea from Kaur and populations from Jayapura, Buton, Wakatobi, Madagascar, India, and Japan, indicating a broad geographic distribution. These results confirm the presence of O. cyanea in Kaur waters and highlight its morphological and genetic similarity to other populations, providing a foundation for future conservation and sustainable fishery practices in the region.